Infectious Disease Outbreak and Post-Traumatic Stress Symptoms: A Systematic Review and Meta-Analysis - Qiu, Dan; Li, Yilu; Li, Ling; He, Jun; Ouyang, Feiyun; Xiao, Shuiyuan (Frontiers in Psychology, 2021)
Background: As one of the most widely researched consequence of traumatic events, the prevalence of post-traumatic stress symptoms among people exposed to the trauma resulting from infectious diseases outbreak varies greatly across studies. This review aimed at examining the pooled prevalence of post-traumatic stress symptoms among people exposed to the trauma resulting from infectious diseases outbreak, summarizing the possible causes of the inconsistencies in the current estimates. Methods: Systematic searches of databases were conducted for literature published on PubMed, EMBASE, Web of Science, the Cochrane Library, PsycArticle, CNKI until 14 October 2020. Statistical analyses were performed using R software. Results: Of 106 studies were included. The results showed that the pooled prevalence of post-traumatic stress symptoms among the general population exposed to the trauma resulting from infectious diseases outbreak was 24.20% (95% CI: 18.54% to 30.53%), the pooled prevalence of post-traumatic stress symptoms among healthcare workers was 24.35% (95% CI: 18.38% to 31.51%), the pooled prevalence of post-traumatic stress symptoms among infectious disease patients was 28.83% (95% CI: 18.53% to 44.86%), and the pooled prevalence of post-traumatic stress symptoms among suspected cases of infectious disease was 25.04% (95% CI: 18.05% to 34.73%). Mortality rate was a significant contributor to heterogeneity. Conclusions: Evidence suggests that post-traumatic stress symptoms were very common among people exposed to the trauma resulting from infectious diseases outbreak. Health policymakers should consider both short-term and long-term preventive strategy of post-traumatic stress symptoms.